Future Prospects for the Application of Artificial Intelligence in Judicial Management - Andrade A, Diego; Toapanta T, Moisés; Gómez D, Zharayth; Mafla G. , Enrique; Orizaga T, Antonio; Jadán G, Janio (Journal of Ecohumanism, 2024)
The problems in judicial management persist regarding the applicability of artificial intelligence (AI) systems. Currently, they have become a challenge as they lack legal foundation and legitimacy, given that to date, only a minimal number of countries have laws addressing the supervision, regulation, management, and control of AI system applicability in judicial settings. The objective of this research is to analyze the future perspectives of the applicability of Artificial Intelligence in Judicial Management. The method employed will be exploratory research to analyze information from reviewed articles, legal reports, and official websites. Possible indicators of issues in AI applicability in judicial management, current and future trends of AI in judicial management, and an appropriate conceptual model for AI applicability in judicial management were identified. It was concluded that the application of artificial intelligence in judicial management remains a challenge and an ongoing issue because it currently does not inspire confidence in decision-making processes.